Efektivitas Pembelajaran Daring Berbasis Inkuiri Melalui Whatsapp Group Terhadap Pemahaman Konsep Benzena dan Turunannya - Mu'minin, Ali Amirul (PSEJ (Pancasakti Science Education Journal), 2022)
This research aims to determine the effectiveness of inquiry-based online learning using WhatsApp Group on understanding the concept of benzene and its derivatives by comparing the level of concept understanding in benzene and its derivatives produced by inquiry-based online learning and expository-based online learning through WhatsApp Group. This research used quasi-experimental design with pretest-posttest control group design. Research sample were 4th semester students of Tadris Kimia IAIN Tulungagung in the 2020/2021 academic year. Research instrument was a test for understanding the concept of benzene and its derivatives which had been valid and reliable. Research data were pretest and posttest scores of understanding the concept of benzene and its derivatives were analyzed using t-test on the SPSS program. The results of the analysis show that there were significant differences in the level of concept understanding in benzene and its derivatives produced by inquiry-based online learning through WhatsApp Group and expository-based online learning through WhatsApp Group. The level of concept understanding in benzene and its derivatives produced by inquiry-based online learning through WhatsApp Group were higher than produced by expository-based online learning through WhatsApp Group.